Self Disclosure In Relationship With Users Of The Dating Tantan Application - Arif Antoni; Anis Endang; Sapta Sari (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the reasons for using the Tantan application in active users of the Tantan application who have worked, to determine the self-disclosure of Tantan application users, and to determine the obstacles of Tantan users in finding a partner. This research is a descriptive qualitative research. The number of informants in this study were 6 people. Data were collected through in-depth interviews, observation, and documentation. The data analysis technique used was the Miles and Huberman model analysis technique which was carried out in 3 stages, namely: data reduction, data presentation, and drawing conclusions and verification. This research reveals that the reason Tantan users are just for fun and just want to make friends from online dating apps. Self-disclosure through Tantan is done to feel closer and more comfortable in the stage of meeting new people. The self-disclosure made by Tantan users who were informants in this study were in the form of age, occupation, hobbies, experiences, family circumstances, and love. The obstacles that Tantan users can find in finding a partner are busy work, easily boredom, closed nature and difficulty opening up.